Mental Health in Lebanon's Triple-Fold Crisis: The Case of Refugees and Vulnerable Groups in Times of COVID-19 - Fouad, Fouad M.; Barkil-Oteo, Andres; Diab, Jasmin Lilian (Frontiers in Public Health, 2021)
Lebanon’s management of the COVID-19 pandemic is largely being maneuvered amid the country’s escalating triple fold crisis. As the country continues to grapple with political stagnation, a dwindling economy and currency, all while working through an ongoing refugee crisis, mental health in times of Coronavirus in Lebanon remains unaddressed. This piece explores the effects of this triple fold crisis upon the mental health of the country’s refugees and most vulnerable groups, and provides room for discussions on the potential benefits of telemental health as an intervention in low-income and conflict settings. Although the implementation of TMH services in Lebanon among vulnerable communities in times of COVID-19 is not a priority, this piece insists it would ultimately fill a substantial mental health gap during the country’s ongoing difficult transitory period.